Beban Kerja Operator Menggunakan Metode CVL dan NASA-TLX PT. Batanghari Barisan - Windi junialdo (Universitas Putra Indonesia YPTK Padang, 2023)
Batang Haribarisan is a company engaged in the processing of raw rubber into semi-finished goods (work in process). The type of product produced is crumb rubber. PT. Batanghari Barisan still has a lot of work that is done manually which can cause workload both physically and mentally, therefore it is necessary to measure the physical and mental workload for workers to find out whether the work carried out is included in the workload category that is safe to do in long period of time. The methods that can be used are the Cardio Vascular Load (CVL) and National Aeronautics and Space Administration Task Load Index (NASA-TLX) methods. It is known that the measurement of physical workload using the CVL method, there is workload in the category that needs to be repaired, namely breaker and hammermill operators, with a percentage of 32.05% and 32.65%. Both types of work require high physical labor because most of the work is done standing, monotonous and repetitive. and secondly, the operator's age is considered old, namely 56 years and 47 years, so that it affects the perceived workload. Based on the results of mental workload calculations using the NASA-TLX method that has been carried out. Whereas the mental workload with indicators is Mental Needs (MD) of 170, Physical Needs (PD) of 540, Time Requirements (TD) of 280, Work Performance (OP) of 390, Level of Effort (EF) of 510, and Frustration Level (FR) of 180.